Rekonseptualisasi Kewarganegaraan Berbasis Negara-Bangsa terhadap Kondisi Masyarakat Multikultural Melalui Pemikiran William Kymlicka: Reconceptualization of Nation-State-Based Citizenship in the Condition of Multicultural Societies Through the Thoughts of William Kymlicka - Ramadhan, Rizqi Akbar; Kartika, Ganang Dwi (Jurnal Filsafat Indonesia, 2025)
The undoubtedly multicultural condition of society encourages reconceptualize efforts of nation-state based citizenship. Nation-state-based citizenship is incompatible with the multiculturalism movement. This research aims to encourage efforts to reconceptualize citizenship in order to synchronize the conditions of multicultural society and the challenges of multiculturalism with the nation-state. Through the interpretation of Kymlicka's concept of multiculturalism and the adoption of the spirit of the cosmopolitanism movement, the researcher proves the urgency of reconceptualizing new citizenship as an effort to readjust to the conditions of multicultural society in order to achieve social compromise within society. Equal community life can only be achieved if there are equal recognition of the community's cultural diversity and the construction of inclusive community solidarity through a conceptual readjustment effort.